Theoretical Study on Hybrid Amplification of 32-Channels DWDM in Optical Parametric Amplifiers - Wan Maisarah Mukhtar; Alia Athira Tarmuji; Noor Syuhaida Mohamed (Penerbit Akademia Baru, 2024)
Non-Indexed Publication